2022
DOI: 10.1155/2022/6468995
|View full text |Cite
|
Sign up to set email alerts
|

Playing with AI to Investigate Human-Computer Interaction Technology and Improving Critical Thinking Skills to Pursue 21st Century Age

Abstract: As part of the human-computer interaction (HCI) that artificial intelligence has, it has a specific effect on developing critical thinking skills, which is what this study is looking at. The purpose of this study was to determine the impact of AI friend apps on EFoLLe (English foreign language learners) interactions with technology. The primary focus of this paper is on a new artificial intelligence-based immersion teaching method for university-level English. Students’ English proficiency and CT are the prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 62 publications
3
8
0
Order By: Relevance
“…The mixed research approach combines elements of both quantitative and qualitative research methods in a single study to gain a more comprehensive understanding of a research topic by integrating numerical data analysis with an in-depth exploration of underlying meanings, contexts, and experiences [58] like the use of AI writing technologies in writing classrooms. Prior researches including Palermo and Wilson [57], Wale [27], Fathi et al [39], Alharbi and Alqefari [40], Abdul et al [34], Muthmainnah Seraj and Oteir [54], and Utami et al [45] have similarly employed a mixed research approach, yielding congruent results that correlate with the findings of the current study as presented in Section 6.…”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…The mixed research approach combines elements of both quantitative and qualitative research methods in a single study to gain a more comprehensive understanding of a research topic by integrating numerical data analysis with an in-depth exploration of underlying meanings, contexts, and experiences [58] like the use of AI writing technologies in writing classrooms. Prior researches including Palermo and Wilson [57], Wale [27], Fathi et al [39], Alharbi and Alqefari [40], Abdul et al [34], Muthmainnah Seraj and Oteir [54], and Utami et al [45] have similarly employed a mixed research approach, yielding congruent results that correlate with the findings of the current study as presented in Section 6.…”
Section: Methodssupporting
confidence: 80%
“…As Muthmainnah Seraj and Oteir [54] investigated, while 19.1% of the students strongly agreed on the relevance of AI writing applications to enhance writing skills, 51.6 agreed, and 27.3 were neutral on the issue. Wang [30] also found that AI writing technologies could motivate students to write more for it is stress-free and entertaining to work online.…”
Section: Students' Perception Towards Integrating Ai Writingmentioning
confidence: 99%
“…The former being said, the capability to accelerate and expand knowledge is still relevant, especially as that capability bears upon a variety of important issues. The first issue is the need to instill critical thinking into students [14,15]. The speed, simplicity, and sheer volume of targeted information may provide an important contribution to the development of critical thinking.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, lecturers play a very important role in ensuring their students are successful in developing language skills at university by providing them with media and technology-based learning. Muthmainnah et al (2022) and Bower et al (2017) stated that educational establishments are rapidly updating their courses to meet students' needs as they grow up in a digital era, with digital learning developments expected to grow exponentially in the coming years. In the EFL teaching process, this standard is being reached more quickly.…”
Section: Discussionmentioning
confidence: 99%